Optimization Optimization of Parallel Solar Water Heater Using Six Flat-Plate Collectors with Stainless Steel Pipes - Wiranata, Anggi; Fuazen; Eko Julianto (Talenta Publisher, 2025)
This study aims to optimize the thermal performance of a parallel-type solar water heating system employing six flat-plate solar collectors with stainless steel pipes. Experimental testing was conducted in Pontianak City, Indonesia, under tropical equatorial conditions during three time sessions from 11:00 AM to 2:00 PM. The system was designed as a passive configuration to enhance heat absorption and uniform flow distribution. Data were recorded at 5-minute intervals, including water temperature variation, solar radiation intensity, and thermal efficiency. The results indicate that the water temperature increased significantly with a temperature difference (ΔT) ranging from 3.4˚C to 13.6˚C, while the thermal efficiency varied between 1.74% and 6.31%, reaching its maximum during the 1:00–2:00 PM session. Solar radiation intensity was observed in the range of 65–89 Lux, which showed a direct influence on system performance. Although efficiency decreased slightly under high thermal load conditions, the overall results demonstrate that the proposed parallel collector configuration performs effectively even in the afternoon period. These findings confirm that a parallel-type flat-plate solar water heater using stainless steel pipes has strong potential as an energy-efficient and environmentally friendly water heating system for tropical regions. Keyword: Solar Water Heater, Flat-Plate Collector, Thermal Efficiency, Stainless Steel Pipe, Renewable Energy